PENGARUH USIA KAWIN MUDA TERHADAP SOSIAL EKONOMI RUMAH TANGGA DESA RANAWANGKO KECAMATAN TOMBARIRI KABUPATEN MINAHASA - Natalia Nino, Crisdeyenti; Sumual, MS, Prof. Tinneke E. M.; Rori, M.Si , Drs. George (Program Studi Ilmu Ekonomi, 2023)
The impact of youth marriage on rural socioeconomic ranowangko tombariri district minahasa. The study is set against a backdrop of many young mating ages that affect domestic socioeconomic conditions. The purpose of this study is to know the impact of young mating age on the ranowangko village's social economy tombariri district minahasa The study employed a quantitative method by making a survey approach using statistical models. The data-gathering technique in this study shows that there are still many young marriage-age marriages.